Literature Circles as a Strategy for Differentiated Instruction in Reading Classroom, how? - Fadhli, Muhammad (La Ogi : English Language Journal, 2025)
This article describes how differentiated instruction can be implemented in the reading classroom using the literature circle strategy. Literature circle strategy provides a structured yet flexible framework that allows students to engage with literary texts in collaborative groups, each assuming specific roles that cater to their individual strengths and learning preferences. The article outlines how teachers can design and manage literature circles to accommodate varied reading levels, interests, and participation styles, making reading activities more inclusive and meaningful. It highlights practical steps such as selecting diverse texts, assigning differentiated roles, and facilitating student-led discussions. By focusing on classroom application, this article offers insights into how literature circles support student engagement, enhance comprehension, and foster a supportive reading environment that aligns with the principles of differentiated instruction.